(untitled) (Global Journal of Medical Research, 2022)
Based on measurements the article claims that individuals living on the principle my way or the highway suffer stress because it cannot always be their way The stress brings with time chronic disease of their genetically inherited weak organ and shortens their lifespan It also brings stress to the lives of their life partners who suffer heart and digestion disorders specific for all of them which shorten their lifespan Our Creator gave us freedom of choice and we should give freedom of choice to the people around us